Optimasi Multi-Response dan Analisis Cost Of Poor Quality pada Proses Powder Coating Menggunakan Metode Taguchi–Grey Relational Analasis (Studi Kasus: CV Aji Batara Perkasa Mandiri Sidoarjo) - Syafril Maulana Arnanda; Erni Puspanantasari Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The powder coating process in automotive component production plays a critical role in determining final product quality. CV Aji Batara Perkasa Mandiri faces high product defect rates (average 11.22%) in the finishing process. This study aims to optimize powder coating process parameters (pretreatment stages, spray gun pressure, nozzle distance, and curing oven temperature) to simultaneously minimize Defect Rate, Rework Rate, and Scrap Rate, and calculate Cost of Poor Quality (COPQ) savings. The method used is the integration of the Taguchi Method and Grey Relational Analysis (GRA) with an L9(3⁴) Orthogonal Array experimental design. Results show that the pretreatment factor is the most dominant parameter (41.09% contribution). The optimal parameter combination obtained is A2B2C3D1 (5-stage pretreatment, 2.5 bar pressure, 25 cm nozzle distance, and 160°C curing temperature). Implementation of these parameters successfully reduced the defect rate to 5.93% (56.46% reduction) and achieved COPQ savings of Rp 23,331,167 per month (61.51%).